PENGUATAN KOMPETENSI CALON GURU TERHADAP MAHASISWA PPL DI SMPN 3 KASIHAN BANTUL YOGYAKARTA - Nur Kholik; Wahit Desta Prastowo; Baiq Ismiati; Endi Rochaendi (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
This study aims to reveal how the PPL program is able to strengthen / strengthen the competence of prospective educators who have been competently mandated in the Teacher and Lecturer law such as; paedagogic competence, professional competence, social competence, and social competence. The types in this study are qualitative research, with a phenomenological approach, with techniques for collecting interview, observation and documentation data. As for data analysis, it uses interactive analysis. So that the results of this service research produce among others; first in the aspect of paedagogic competence; PPL students are able to understand curriculum terms, learning indicators, prepare lesson materials, master teacher knowledge and students are also able to master the knowledge they teach. Second, aspects of professional competence; PPL students have self-confidence, have consequences and preparation in the profession, and always evaluate themselves. Third, the aspect of social competence; PPL students have the ability to communicate, the ability to organize. Fourth, aspects of personality competence; PPL students are actually skilled in organizing the order of materials, skilled in preparing learning materials, skilled in formulating learning indicators, mastering teacher knowledge, and mastering the knowledge they teach